DEVELOPMENT OF INTERACTIVE LEARNING MEDIA IN SCIENCE LEARNING BASED ON SOCIO-SCIENTIFIC ISSUES (SSI) TO IMPROVE DIGITAL LITERACY OF JUNIOR HIGH SCHOOL STUDENTS - Sa’diyah, Halimatus; Wicaksono, Iwan; Rusdianto, Rusdianto (Universitas Muhammadiyah Mataram, 2025)
This study aims to produce interactive learning media based on Socio Scientific Issues on Ecology and Biodiversity material that is valid, practical, and effective to improve digital literacy of junior high school students. This research uses the ADDIE development model. The data collection techniques used were observation, interview, validation sheet, media usage implementation sheet, digital literacy assessment rubric, student response questionnaire, and documentation. The results of the validation data analysis obtained a validation value of 92% with a very valid category which includes aspects of content validation, language, and graphics. The practicality analysis results obtained a value of 95% with a very practical category. The results of the effectiveness analysis based on indicators of digital literacy skills obtained n-gain of 0.50 with a moderate category. The results of the effectiveness analysis seen from the student questionnaire obtained a score of 92% in the very good category. Thus, the SSI-based interactive learning media product developed is said to be valid, practical and effective to be applied to junior high school science learning to improve digital literacy of junior high school students.